Determination of L-shell fluorescence parameters of thallium in thallium compounds. Issue 4 (21st April 2021) - Cengiz, Erhan; Tıraşoğlu, Engin; Apaydın, Gökhan; Köksal, Oğuz Kağan
Abstract: The Li ( i  =  l, α, β, and γ ) production cross-sections, L-shell average fluorescence yields, and Coster-Kronig vacancy transfer factors for L3 subshell X-rays of thallium in some thallium compounds were determined using Energy Dispersive X-ray Fluorescence spectrometer. The compounds were excited by 59.5 keV gamma-rays from an Americium-241 annular radioactive source, and the L X-rays emitted by the compounds were counted using an ultra-low energy germanium detector with a resolution of 150 eV at 5.9 keV. The production cross-sections, average fluorescence yields, and Coster-Kronig vacancy transfer factors of thallium in these compounds were compared with theoretical calculations and available experimental values of the pure thallium.